The Effect of Communication, Leadership, Incentives and Competence on Performance of Transportation Service Employees, Labuhanbatu District - Harapan Putra Lase; Marlina Siregar; Rizki Syahputra (Budapest International Research and Critics University, 2022)
This research was conducted at the Department of Transportation of Labuhanbatu Regency, with the aim of analyzing the effect of communication, leadership, incentives, and competence on employee performance. This study uses quantitative methods with the following analytical techniques, classical assumption test, multiple linear regression test, hypothesis testing, and coefficient of determination test. The results of data analysis in this study can be described with the following explanation, vThe communication variable (X1) has a value of tcount (3.06) > ttable (1.66) with a significantly smaller value than the probability value of 0.05 or a significant value of 0.003 <0.05. Thus, it can be concluded that the communication variable (X1) has an effect on positive and significant on employee performance. Leadership (X2) has a value of tcount (3.44) > ttable (1.66) with a significantly smaller value than the probability of 0.05 or 0.001 <0.05. Thus, it can be concluded that leadership (X2) has a positive and significant effect on performance. employee. Incentive (X3) has a value of tcount (5.39) > ttable (1.66) with a significantly smaller value than the probability of 0.05 or 0.000 <0.05. Thus, it can be concluded that the incentive (X3) has a positive and significant effect on performance. employee. Competence (X4) has a value of tcount (10.30) > ttable (1.66) with a significantly smaller value than the probability of 0.05 or 0.000 <0.05. Thus, it can be concluded that competency (X4) has a positive and significant effect on performance. employee. The results of the F test have an Fcount of 172.59 > Ftable 2.49 with a significance value of 0.000 <0.05. From these results, it can be concluded that communication, leadership, incentives, and competence simultaneously have a positive and significant effect on employee performance.